Levels of IL-6 and IL-8 in complicated versus uncomplicated urinary tract infection - Ahmed, Maryam Alaa; Ahmed, Mohaned Muhsen; Ali, Ali Jaleel (International Journal of Biological Research, 2024)
Background: Urinary tract infections (UTIs) are one of the world's most frequent infectious diseases, affecting 150 million people each year and resulting in severe morbidity and high medical expenditures. UTIs can be clinically defined as uncomplicated UTIs (uUTIs) or complicated UTIs (cUTIs) to differentiate infections of benign origin from those with a higher risk of recurrence or progression to severe pathology. The aim of this study was to evaluate interleukin-6 (IL-6) and IL-8 as potential biomarkers in differentiating complicated and uncomplicated Methods: Ninety samples of urine were collected. There were 43 samples from healthy controls and 47 samples from UTI patients, those who have been clinically diagnosed with UTIs by the urologist. The serum IL-6 and IL-8 were measured using an enzyme-linked immunosorbent assay and commercially available kits. Results: The levels of both IL-6 and IL-8 were significantly higher in UTI patient then in control subjects (p=0.001, p=0.001). A significant difference was observed in the mean of level IL-6 between culture positive UTI patients and culture negative UTI patients (p=0.014). In addition, the type of bacterial growth, a significant difference was observed in the mean of serum IL-6 and IL-8 level in UTI caused by gram negative bacteria in comparison with UTI caused by gram positive bacteria. Conclusion: High levels of IL-6 are associated with the growth of gram-negative bacteria, and this indicates that gram-negative bacteria could induce stronger inflammatory responses than gram-positive bacteria. IL-8 levels are higher in UTIs caused by gram-negative bacteria. This result further supported the evidence that gram-negative bacteria are potent inducers of inflammatory responses.